(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The process of normal human childbirth is categorized in three stages of labor: the shortening and dilation of the cervix, descent and birth of the infant, and delivery of the placenta. Oxytocin is the most commonly used agent for induction, and is used to induce uterine contractions. Objective:To estimate the efficacy of oral misoprostol for labor induction. Methods: This randomized, controlled trial study was comparing intravenous oxytocin to a 25-microgram dose of oral misoprostol every 3-4 hours. A woman who had cervical dilation of 0-2 cm then undergoes labor induction. Our outcome was recorded. Results:we found when we used misoprostol the time duration was significantly less specially in primigravida and when os closed, the side effect approximately same as oxytocin. Conclusion:Oral misoprostol is an effective agent for inductionof labor. Keywords:Induction of labor, misoprostol, oxytocin